The Qingchangligan Formula Alleviates Acute Liver Failure by Regulating Galactose Metabolism and Gut Microbiota - Yin, Ruiying; Liu, Shuhui; Jiang, Xuejiao; Zhang, Xiangying; Wei, Feili; Hu, Jianhua (Frontiers in Cellular and Infection Microbiology, 2022)
The Qingchangligan formula (QCLGF) is a traditional Chinese medicine that has significant clinical potential for patients with acute liver failure (ALF). However, the experimental evidence of the effect of QCLGF on ALF and the associated mechanisms remain elusive. We aimed to evaluate the function of QCLGF in ALF and the underlying mechanism. ALF was induced in rats by intraperitoneal injection of D-GalN (1100 mg/kg). The Qingchangligan formula was administered to the rats (6.725g/k g · d) for 5 days，and the model group and the control group were given the same amount of physiological saline. Then 16S rRNA gene sequencing, high performance gas chromatography-mass spectrometry (GC-MS), and RNA-seq analysis were performed on the samples. The levels of ALT and AST in the ALF rats were abnormal (5322.08 ± 566.27 and 7655.95 ± 1238.08, respectively) compared with the normal control (98.98 ± 6.90 and 99.63 ± 10.94, respectively). The levels of ALT and AST in the QCLGF rats (2997.67 ± 469.24 and 4158.40 ± 596.07, respectively) were closer the normal control group. Liver HE staining showed that the degree of liver damage in the QCLGF rats was lighter than that in the ALF rats. The overall structure of the gut microbiota after ALF was significantly altered, including Proteobacteria, Blautia, Romboutsia, Parabacteroides, UCG-008, Parasutterella, Ruminococcus, norank_f__Lachnospiraceae, the Eubacterium_xylanophilum_group, Oscillibacter, and Eisenbergiella. QCLGF balanced the structure and abundance of intestinal flora. The levels of D(+)galactose, isopropyl beta-D-1-thiogalactopyranoside and D-mannitol were lighter in the plasma of the ALF rats than in the normal control rats, but there were significantly elevated levels of those metabolites in the QCLGF rats. The gene expression changed significantly in the ALF rats. QCLGF regulated the expression of Thbs1 and the KEGG pathways of carbohydrate metabolism, lipid metabolism, signal transduction, the immune system, and infectious disease: bacterial. QCLGF may alleviating intestinal flora disorder, regulating galactose metabolism and downregulating the expression of THBS1 to alleviate d-GALN induced acute liver failure.